THE INFLUENCE OF INTERNATIONAL LAW ON TIMOR LESTE'S ECONOMIC POLICY - Carolina da Cruz (LPPM STIH Awang Long, 2026)
International law respects the important role of state territory as reflected in the principle of respect for the integrity and sovereignty of a state territory (territorial integrity and sovereignty) contained in various products of International Law. This study uses normative research methods. The data and information in this research are primary and secondary data. The nature of this research is descriptive-analytical. Based on the results of this study, international law has a significant influence on the formulation and implementation of Timor Leste's economic policy, especially considering its unique history as a new country and its dependence on global cooperation and foreign aid. The norms contained in the bilateral trade agreement between Indonesia and Timor Leste significantly affect local economic sovereignty in border areas, with both positive and negative impacts. This influence is particularly felt in the economic dynamics of communities that are highly dependent on cross-border activities.